Development and volume growth of organized derivatives trade in emerging markets - Treviño Villarreal, María de Lourdes (UANL. Facultad de Economía, 2005)
This paper updates and extends reviews of the development of emerging market derivatives exchanges for a sample of 58 emerging countries and 83 derivatives exchanges from 1999 to 2005. Active exchanges are found in 29 emerging market countries, mostly trading financial products. Volume concentration measures suggest that smaller exchanges have increased their market shares outpacing larger ones. This is confirmed by a clear and significant reduction in the concentration index between developed and emerging market exchanges in favor of the latter. Non-US exchanges have dominated US counterparts, while trade has increasingly concentrated on financial derivatives rather than commodities. Exchange-traded derivatives showed a greater concentration than OTC markets, although these described a faster increase in concentration levels.